Advances in environmental accounting & management. Vol. 1 - Freedman, Martin; Jaggi, Bikki (Emerald, 2000)
List of Contributors. Ad Hoc Reviewers. Editorial (M. Freedman, B. Jaggi). Environmental accounting, managerialism, and sustainability: is this planet safe in the hands of business and accounting? (R. Gray, J. Bebbington). A multi-case investigation of environmental legitimation in annual reports (A. Savage et al.). The environment and the accountant as an ethical actor (M.A. Reynolds, M.R. Mathews). Changing superfund disclosure and its relation to the provision of other environmental information (D. Patten). An examination of the relevance of ISO 14000 Environmental Standards: a survey of US corporations (Z. Rezaee, J. Szendi). Do environmental disclosures in US annual reports differ by environmental peformance? (S. Hughes et al.). Determinants of social responsibility disclosure of US fortune 500 firms: an application of content analysis (F. Alnajjar). Disclosure of environmental information by Canadian manufacturing companies: a voluntary disclosure perspective (K. Bewley, Yue Li).
Keywords: Environmental auditing.; elektronické knihy; electronic books